Subsurface soil moisture estimation by VI-LST method - Holzman, Mauro Ezequiel (2014)
In this letter, the relationship between temperature vegetation dryness index (TVDI) from the Moderate Resolution Imaging Spectroradiometer and subsurface soil moisture (SM) cover crop and native grassland of the Argentine Pampas is analyzed.High correlation (R2 > 0.69) between TVDI and SM measurements was found at different soil depths. In addition, we found that the potential of this index to reflect subsurface soil wetness fluctuations depends on root system depth, root distribution in the soil, and physical soil characteristics. Results indicate that thermal and reflectance data combination could be used to monitor subsurface SM below vegetated areas.